EFFICACY OF LIGNOCAINE IN DENTAL EXTRACTIONS - PRATISHTA JAIN; NABEEL NAZAR (International Journal of Pharma and Bio Sciences, 2014)
Dental extractions are associated with pain and therefore require potent local anesthetics that can keep the patient comfortable during the procedure. Lignocaine is available for more than half a century and is still being widely used in clinical practice even with the advent of newer anesthetic agents. It is also a standard of comparison for newer anesthetic agents. The systemic effects of the anesthetic agents also has to be considered when administering these drugs. The drug with the most potent anesthetic effect and least systemic toxicity is considered the most ideal. Inspite of extensive studies, the ideal agent is still debatable. The efficacy of lignocaine in dental extractions is reviewed here